Response of superconductivity and crystal structure of LiFeAs to hydrostatic pressure. - Mito, M; Pitcher, M; Crichton, W; Garbarino, G; Baker, P; Blundell, S; Adamson, P; Parker, DR; Clarke, S (2009)
On the application of hydrostatic pressures of up to 1.3 GPa, the superconducting transition temperatures (T(c)) of samples of LiFeAs are lowered approximately monotonically at approximately -2 K GPa(-1). Measurements of the X-ray powder diffraction pattern at hydrostatic pressures of up to 17 GPa applied by a He gas pressure medium in a diamond anvil cell reveal a bulk modulus for LiFeAs of 57.3(6) GPa which is much smaller than that of other layered arsenide and oxyarsenide superconductors. LiFeAs also exhibits much more isotropic compression than other layered iron arsenide superconductors. The higher and more isotropic compressibility is presumably a consequence of the small size of the lithium ion. At ambient pressure the FeAs(4) tetrahedra are the most compressed in the basal plane of those in any of the superconducting iron arsenides. On increasing the pressure the Fe-Fe distance contracts more rapidly than the Fe-As distance so that the FeAs(4) tetrahedra become even more distorted from the ideal tetrahedral shape. The decrease in T(c) with applied pressure is therefore consistent with the observations that in the iron arsenides and related materials investigated thus far, T(c) is maximized for a particular electron count when the FeAs(4) tetrahedra are close to regular.